Kepemimpinan Budi Karya Sumadi dalam Transformasi Transportasi Nasional: Studi Kasus Whoosh dan Tol Laut - Yuanni Ramadana; Sarah Dwi Aulia; Dhea Ananda; Reyhan .; Yulia Hanoselina (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
As an archipelagic country with more than 17,000 islands, Indonesia has ongoing structural connection gaps, as evidenced by national logistics costs that account for 23 and 24 percent of GDP and regional differences in food prices that can exceed 300 percent in the east. Using the Khan-Hilton transformational leadership framework, which includes idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration, this study examines the transformational leadership of Budi Karya Sumadi as Minister of Transportation (2016–2024) through a comparative case study of the Jakarta–Bandung Whoosh High-Speed Rail and the Sea Toll (Tol Laut) program. Data were gathered from peer reviewed journals, official policy papers, and government reports published between 2018 and 2024 using a qualitative descriptive strategy that included focused content analysis and a systematic literature review. The results show that Whoosh, which began full operation on October 17, 2023, and served over 5.4 million passengers in its first year despite ongoing financial sustainability challenges from its US$7.2 billion investment, is a prime example of intellectual stimulation and idealized influence through high-technology innovation. Although backhaul inequities still exist, Tol Laut, which grew from 3 routes in 2015 to 39 routes in 2023 and reduced commodity pricing discrepancies by 12.18 percent by 2022, is a prime example of customized consideration and inspirational motivation through spatial justice. The study comes to the conclusion that in order to guarantee long-lasting policy change, effective transformational leadership necessitates ongoing institutional commitment beyond individual tenure.